COMPACTION ANALYSIS OF STONE MATRIX ASPHALT MIXTURE USING MARSHALL COMPACTION AND SUPERPAVE GYRATORY COMPACTOR ON MODULUS RESILIENT VALUE AND RESISTANCE TO RUTTING - Giani Hadiastari, Icha
Stone Matrix Asphalt (SMA) is a hot mix asphalt mixture specially formulated to increase durability, skid resistance, strength, durability, and rutting resistance. The Specifications of the Ministry of Public Works 2018 for the SMA mixture were compacted using Marshall, while Marshall compaction was deemed less effective due to changes in the size of the coarse aggregate due to the impact Marshall load, resulting in changes in the gradation of the SMA mixture. Another compaction method is The Superpave Gyratory Compactor (SGC). The main parameters of the SGC tool are the number of rotations, rotation angle, vertical pressure, and rotation speed. The SGC’s design method can reduce the fragmentation of coarse aggregates, because the SGC forms specimens by rotating while applying vertical pressure, this method allows the SMA mixture that forms the aggregates to move with each other, so that the voids can be filled quickly. The purposes of this research are to analyze the compaction of SMA mixture using Marshall compaction and SGC to the value of resilient modulus, rutting and analyze the use of SGC specification compaction for Stone Matrix Asphalt (SMA) mixtures using specification Bina Marga 2018 revision 2. This testing begins with testing the properties, followed by the manufacture of test objects using Marshall compaction based on Bina Marga 2018 Specifications and Marshall compaction based on AASHTO M325. Then resilient modulus test using UMATTA tool and rutting test using Hamburg Wheel Tracking Device in dry and wet conditions Based on the properties testing, the aggregate and asphalt have met the specifications. The SMA mixture compacted using the Marshall Bina Marga 2018 Specification has a higher VMA value than the AASHTO M325 Specification for SGC compaction method. The Marshall compaction VIM value range is 3 – 5% while the SGC is only 4%, this affects the voids content and OAC values in each method.. Based on the AASHTO M325 Specification for a mixture of SMA which was compacted using the SGC method with 100 gyrations, the OAC value obtained was greater than the OAC value for a mixture of SMA which was compacted using the Marshall method using the Specifications of the Ministry of Public Works 2018. This is due to the increasing density value and compaction efforts to get VIM 4 will be easier. The difference of resilience modulus value of Marshall compaction and SGC is 109 Mpa. The SGC compaction resilience modulus value of the AASHTO specification is close to the compaction modulus resilience value of Marshall specification Bina Marga 2018.Based on HWTD test result, the mixture of SMA with SGC with a variation of 125 gyrations is more resistant to rutting than compaction using Marshall. This is evidenced by the higher value of the Resilient Modulus of the SMA mixture with the SGC compaction method compared to the Marshall compaction method, so that the mixture will be stiffer and more resistant to rutting. The dynamic stability value using the SGC compactor has a higher value than the specification of Bina Marga 2018. Based on the characteristic value of the specification Bina Marga 2018, if using an SGC compactor, it is recommended that the SGC parameter value be 1.16? rotation angle, 116 rounds of rotation, 600 kPa pressure, and a speed of 30 revolutions/minute.